Biogeographic constraints to marine conservation in a changing climate. Issue 1 (7th February 2018) - Fredston‐Hermann, Alexa; Gaines, Steven D.; Halpern, Benjamin S.
Abstract: The siting of protected areas to achieve management and conservation objectives draws heavily on biogeographic concepts of the spatial distribution and connectivity of species. However, the marine protected area (MPA) literature rarely acknowledges how biogeographic theories underpin MPA and MPA network design. We review which theories from biogeography have been incorporated into marine spatial planning and which relevant concepts have yet to be translated to inform the next generation of design principles. This biogeographic perspective will only become more relevant as climate change amplifies these spatial and temporal dynamics, and as species begin to shift in and out of existing MPAs. The scale of climate velocities predicted for the 21st century dwarfs all but the largest MPAs currently in place, raising the possibility that in coming decades many MPAs will no longer contain the species or assemblages they were established to protect. We present a number of design elements that could improve the success of MPAs and MPA networks in light of biogeographic processes and climate change. Biogeographically informed MPA networks of the future may resemble the habitat corridors currently being considered for many terrestrial regions.